2002
DOI: 10.1117/12.452487
|View full text |Cite
|
Sign up to set email alerts
|

Single and three pulse photoselection of dye probes in nematic liquid crystals

Abstract: We present results of single and three pulse photoselection studies of the dynamics of a fluorescent probe (Oxazine 4) in the nematic phase of the liquid crystal 4-n-pentyl-4'-cyanobiphenyl (5CB). The combination of these techniques with time resolved fluorescence anisotropy measurements allows the unambiguous determination of the full angular motion of the probe together with the ground and excited state degrees of equilibrium (steady state) alignment. The restricted JHRPHWU\ LPSRVHG E\ WKH QHPDWLF KRVW LV VH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Considerable detail that could be explored in fluorescence lifetime and anisotropy studies is thus lost. The interaction of polarized light with an ordered molecular array has been shown to yield information on detailed local order and the full angular motion of a molecular probe [6][7][8][9][10]. The local environment on average experiences wholly unpolarized excitation and the possibility of distinguishing between θ and φ orientations (and motions) within the probe environment is lost ( [11] and A.J.…”
Section: Conventional Fluorescence Techniques: Limitations and Constrmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable detail that could be explored in fluorescence lifetime and anisotropy studies is thus lost. The interaction of polarized light with an ordered molecular array has been shown to yield information on detailed local order and the full angular motion of a molecular probe [6][7][8][9][10]. The local environment on average experiences wholly unpolarized excitation and the possibility of distinguishing between θ and φ orientations (and motions) within the probe environment is lost ( [11] and A.J.…”
Section: Conventional Fluorescence Techniques: Limitations and Constrmentioning
confidence: 99%
“…This loss of information is potentially serious: recent studies in our group of fluorescent probe dynamics within ordered hosts have shown that the imposition of order has a profound influence on rotational diffusion dynamics. A marked difference in θ and φ diffusion rates and their temperature dependence is observed [10,12,13]. The second limitation arises from the selection rules for spontaneous electric dipole transitions, which restrict the degree of order that can be probed in the excited state.…”
Section: Conventional Fluorescence Techniques: Limitations and Constrmentioning
confidence: 99%
See 1 more Smart Citation